2009
DOI: 10.1016/j.mambio.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns of small mammals in the Zambales Mts., Luzon, Philippines

Abstract: In 2004 and 2005, we conducted a survey of the small mammals on Mt. Tapulao ( ¼ Mt. High Peak, 2037 m) in the Zambales Mountains, Luzon Island, Philippines in order to obtain the first information on the mammals of this newly discovered center of endemism. We also tested two hypotheses regarding the relationship of species richness with elevation and the impact of alien species on native mammals. The survey covered five localities representing habitats from regenerating lowland rain forest at 860 m to mossy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…8). It is readily distinguishable from S. musseri by the following combination of dental features: (1) longer maxillary molar tooth row (shorter in S. musseri); (2) broader M1 (narrower); and (3) narrower incisors at their tips (broader), and from S. kalinga and S. montanus through targeted surveys of isolated mountains and mountain chains, using multiple sampling procedures to ensure detection of species that have varied food and foraging habits in different habitats along the elevational gradient (e.g., Balete et al, 2009;Heaney et al, 2011;Rickart et al, , 2011b. In the case of Archboldomys and Soricomys, the use of live earthworms as bait, the targeting of montane and mossy forest at high elevations, and surveys of even small mountain chains, have been crucial in detecting the animals.…”
Section: Soricomys New Genus Type Species: Archboldomys Kalingamentioning
confidence: 99%
“…8). It is readily distinguishable from S. musseri by the following combination of dental features: (1) longer maxillary molar tooth row (shorter in S. musseri); (2) broader M1 (narrower); and (3) narrower incisors at their tips (broader), and from S. kalinga and S. montanus through targeted surveys of isolated mountains and mountain chains, using multiple sampling procedures to ensure detection of species that have varied food and foraging habits in different habitats along the elevational gradient (e.g., Balete et al, 2009;Heaney et al, 2011;Rickart et al, , 2011b. In the case of Archboldomys and Soricomys, the use of live earthworms as bait, the targeting of montane and mossy forest at high elevations, and surveys of even small mountain chains, have been crucial in detecting the animals.…”
Section: Soricomys New Genus Type Species: Archboldomys Kalingamentioning
confidence: 99%
“…Several species of human-commensal rodents and shrews have also been dispersed throughout the region. Their ability to invade native forests is largely unknown, but studies in the Philippines suggest that alien species are unable to penetrate undisturbed or regenerating forests with a rich native small mammal fauna (Balete et al 2009). …”
Section: Near-oceanic Islandsmentioning
confidence: 99%
“…Most of the islands are volcanic in origin and have had no dry-land connection to the Asian continent throughout their geological lifespan (Heaney, 1986;Hall, 1998). Previous surveys have shown that each major island (or set of closely adjacent islands that were connected to each other during the last glacial maximum) is a unique center of mammalian diversity, with levels of endemism ranging from 40% to nearly 90% (Heaney, 1986;Heaney & Regalado, 1998;Catibog-Sinha & Heaney, 2006;Balete et al, 2009). Additionally, each major island has a unique history of geologic processes that resulted in isolated mountain ranges and peaks of differing elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these areas has been shown to harbor a distinct set of mammals and each is recognized as a subcenter of mammalian endemism Heaney et al, 1999;Ong et al, 2002;Duya et al, 2007;Balete et al, 2009, this volume). Additional mountain ranges and isolated peaks on Luzon are part of our ongoing effort to locate and document all of the subcenters of endemism (e.g., Balete et al, 2009;. This paper constitutes the first documentation of the ecology and diversity patterns of mammals on another mountain range on Luzon, the Caraballo Mountains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation